Evaluating the Effectiveness of Smart Irrigation Systems in Improving Agricultural Productivity - Aria Julianto Pratama; Rully Mandela (Agriculture Journal, 2024)
This research aims to evaluate the effectiveness of smart irrigation systems in increasing agricultural productivity in a specific area. The study used a group randomised design (RAK) with two main treatments: Treatment 1 (P1): Use of IoT-based smart irrigation system. The results show that smart irrigation significantly increased crop productivity (34.9% higher than traditional irrigation systems) through precision watering that matches crop needs. Water savings of up to 47.8% prove that the system is able to optimise the use of water resources, while supporting agricultural sustainability. Smart irrigation systems are proven to be more effective than conventional irrigation in improving crop productivity, water resource efficiency and economic returns.